1982
DOI: 10.1111/j.1365-2141.1982.tb07293.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo stimulation and inhibition of granulopoiesis: the effect of an inflammatory reaction on murine diffusion chamber granulopoiesis

Abstract: Humoral factors influencing granulopoiesis have been evaluated using diffusion chambers (DC) implanted in the peritoneal cavity of mice challenged by an aseptic abscess produced by the subcutaneous implantation of copper rods. This resulted in an increase in peripheral blood neutrophils and an increase in tibial granulocytic elements. When DC loaded with bone-marrow cells were implanted into mice stimulated the day before by an aseptic abscess significantly more CFU-s, CFU-c, proliferative and non-proliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…This model allows one to study in vivo, by culture in diffusion chambers, the mechanisms of haematopoiesis in response to acute inflammation. Previous studies have shown that aseptic abscess formation is associated with an increase in the cellular content of diffusion chambers, including proliferative and non-proliferative granulocytes, macrophages, CFU-S and CFU-GM (Symann et al 1982). The present study demonstrates that cell proliferation in diffusion chambers depends on the importance of inflammation.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This model allows one to study in vivo, by culture in diffusion chambers, the mechanisms of haematopoiesis in response to acute inflammation. Previous studies have shown that aseptic abscess formation is associated with an increase in the cellular content of diffusion chambers, including proliferative and non-proliferative granulocytes, macrophages, CFU-S and CFU-GM (Symann et al 1982). The present study demonstrates that cell proliferation in diffusion chambers depends on the importance of inflammation.…”
Section: Discussionsupporting
confidence: 71%
“…The findings elicited in diffusion chambers are relevant to the findings in the host haematopoietic system. Previous studies have shown that blood neutrophil counts, as well as numbers of marrow myeloid and progenitor cells are significantly increased in mice stimulated by an inflammation (Symann et al 1982, Hamood et al 1985. The effects on host haematopoietic cells are comparable to those on the diffusion chamber cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, production of haematopoietic cytokines that we did not measure, could have been stimulated to a different degree by VLB and CY, thus explaining the lack of perfect correlation between the present cytokine and granulocytopoiesis results in mice given cytotoxic treatment. Other investigators have also stimulated haematopoiesis in diffusion chambers, with injections of lithium carbonate (25) or implantation of copper rods as in the present study (7), but without being able to measure raised levels of CSF in the chambers.…”
Section: Discussionmentioning
confidence: 84%
“…Pretreatment of host animals with either irradiation or chemotherapeutic agents causing cytopenia leads to enhanced cell production in intraperitoneally implanted DCs concomitant with hematopoietic cell recovery in the bone marrow and spleen [8,13,22,. Similar stimulation occurs following induction of an aseptic inflammation [92,931 or administration of lithium [94,951 or corticosteroids [96]. Activity produced by antigen-or Schistosomu munsoni-stimulated lymphoid cells [97,98] seems to be a good source of an eosinophilopoietic factor.…”
Section: Humoml Effectsmentioning
confidence: 93%